Menghitung Harga Saham Sebagai Dasar Melakukan Investasi - Muhammad Supriyadi (EBBANK, 2022)
Investing in stocks is strongly influenced by the value of the stock itself. Investors need to pay attention to dividends and earnings are expected to come from the company's future. Besides, it is also important to consider trading activity in the stock market, because of the price activity potential will be more dynamic than static activities that the potential to get bigger gain. Return or required rate of return of an investment will also affect the decision invesatsi, the higher the expected return on stocks will be more selective which includes consideration to investments. All of the above will be reflected in the value or price of the stock is formed. So the decision to invest in stocks or when to do what is determined by the stock price.